Stroke placement in women`s professional tennis: What`s after the serve? - Born, P.; Malejka, L.; Behrens, M.; Grambow, R.; Meffert, D.; Breuer, J.; Vogt, T. (International Journal of Racket Sports Science, 2021)
The aim of the present study was to investigate the placement of the return, and the 3 rd and 4 th strokes in professional women`s tennis, the possible differences related to the level of play and to derive practical recommendations from the results. In total this study contains an examination of 2562 returns, 2065 3 rd strokes and 1606 4 th strokes from 28 players in 19 professional women`s tennis matches (WTA & ITF 2018-2020 season). All strokes were classified using a specific court division method taking outcome (i.e., in, out, net) and placements into account for statistical analyses. Results show that returns are mainly placed into the court`s middle zones whereas 3 rd strokes are placed more into offensive zone groups with 4 th strokes similarly placed but more scattered. No correlation was found between the placement of the return and the 3rd stroke. Correlations were found between the placement of 4 th stroke and the return, between the 4 th and the 3 rd stroke as well as between WTA and ITF players regarding all three strokes (return, 3 rd stroke, 4 th stroke). Present findings may be of interest to female tennis players and their coaches aiming to improve practice patterns in training and competitive performance in matches.